FINANCES OF LOCAL SELF-GOVERNMENT IN WARTIME CONDITIONS: RESENT TRENDS, CHALLENGES, PROBLENS AND PATH OF DEVELOP - HLUSHCHENKO, Olga; SHVAIKO, Mariana; YEROMENKO, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article examines the complex process of adapting the financial system of local self-government in Ukraine under conditions of war and post-war recovery. The primary focus is on the challenges faced by local communities due to significant reductions in budget revenues, which necessitate new approaches to financial management. Examples of effective innovative solutions, such as the implementation of electronic auctions and digital management systems, are provided, enabling communities to enhance financial resilience even in crisis situations. The authors emphasize the importance of diversifying the sources of local budget revenues to ensure stability during wartime and post-war periods. Specifically, the article considers the potential development of municipal enterprises, local taxes, fees, and green tourism as new revenue sources that can support local budgets in times of economic crisis. Additionally, the article underscores the significance of cooperation between communities for resource  conservation and attracting additional investments in joint infrastructure projects. Special attention is given to the necessity of reforming inter-budgetary relations in Ukraine, which should account for new economic realities and promote the efficient allocation of resources among communities. In the conclusions, emphasis is placed on the need to develop the financial autonomy of local self-government, allowing communities to more effectively utilize funds and foster sustainable economic development at the local level.
Keywords: Finance; budget expenditures; management mechanism; public finance; digital technologies; local self-government